Need For Policy Measures to Address the Issues and Challenges Faced by Female Home-Based Workers. - Uzooba Hureem (Journal of Research in Social Science and Humanities, 2026)
In South Asia, especially in Pakistan, the majority of the female labour force is engaged in home-based work compared to men. As it is the most convenient form of work for females, due to cultural restrictions, they are not allowed to go outside their homes without a male companion. In Pakistan, female home-based workers make substantial contributions to the national economy through their wages. Despite their significant contribution, they are facing many challenges that hinder their economic participation.  They are deprived of decent work opportunities and all other work benefits received by formal employees and workers. They are engaged in economic activities to improve their socioeconomic status and meet their household needs. The government needs to consider female home-based workers’ huge contribution toward poverty elimination and national GDP, and establish policy measures to address their issues and challenges to increase their economic participation and enhance women’s economic empowerment. The main objective of this study is to analyze issues of Female Home-based Workers, the significance of addressing their needs to make them more effective for the national economy. The study also suggests the required policy parameters to address the challenges of this substantial workforce.